Influência da perda óssea, tipo de retentor e presença de remanescente coronário no comportamento biomecânico de caninos superiores tratados endodonticamente - Roscoe, Marina Guimarães (2013)
The presence of bone loss is related to changes in the biomechanical behavior of endodontically treated teeth. The purpose of this study was to evaluate the effect of alveolar bone loss, ferrule presence and post type on the biomechanical behavior of endodontically treated maxillary canines restored with all-ceramic crowns. For the experimental analysis, forty upper human canines were selected and divided into 8 experimental groups according 3 treatment variations: bone support, without or with 5.0 mm of bone loss; ferrule presence, with or without 2.0mm of ferrule; and post type, restored with cast post and cores or glass fiber post. The restored canines were loaded at a 15- degree angle, and the deformation was measured using strain gauges placed on the buccal and proximal root surfaces. Strain results were analyzed by 3- way-ANOVA and Tukey HSD tests (α=.05). For the finite element analysis, eight 3-D models were created, following the same variations of the experimental analysis. The models were analyzed using the maximum principal stress criteria for stress distribution analysis. The presence of ferrule decreased significantly the buccal and proximal strain. The type of post showed slightly influence on the stress distribution. The presence of bone loss increased significantly the stress concentration and strain values in both regions mainly on root dentin and surrounding cortical bone. Can be possible to conclude that the presence of a ferrule improved the mechanical behavior, irrespective of the type of post. The 5.0mm of bone loss increased significantly the stress concentration and the strain on the root dentin.